A chicken farm environmental monitoring system
By using an environmental monitoring system composed of Ga2O3/Mo2Ti2AlC3 sensors powered by TENG in chicken farms, the problem of high cost and inability to monitor ammonia concentration in the existing technology is solved, achieving real-time monitoring and cost reduction.
Patent Information
- Application Number
- CN202411488070.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing chicken farms have high real-time monitoring systems and cannot effectively monitor ammonia concentrations, resulting in a decrease in the health and productivity of the chicken flock.
Adopt a chicken farm environment monitoring system consisting of GA2O3/MO2TI2ALC3 sensor supplied by a friction nanometer. The movement terminal is displayed.
Real-time monitoring of ammonia concentration in chicken farms is achieved, reducing system costs, improving chicken health and production efficiency, and reducing harm to the environment.
Smart Images

Figure CN119000803B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of environmental monitoring, and in particular to an environmental monitoring system for a chicken farm. Background Art
[0002] Poultry has a short digestive tract and low digestibility. 20%-25% of nutrients cannot be digested and absorbed by the body and are excreted with excrement. The protein in the excrement is decomposed by microorganisms, releasing a large amount of ammonia. When the ammonia concentration in the blood of poultry reaches 1%, it can cause central nervous system poisoning, which will cause the chickens to be depressed, eat less, and significantly reduce their growth rate and egg production. Therefore, monitoring low-concentration ammonia in chicken farms and timely ventilation play a vital role in improving the growth rate and egg production of chickens.
[0003] If the distributed ammonia sensors in large chicken farms are powered by wires, it will cause problems such as complex wiring, so most of the distributed sensors are currently powered by batteries. However, the batteries need to be replaced regularly, which will incur high labor costs, and will also bring problems such as high recycling costs and environmental pollution. If it is possible to replace the distributed small batteries and monitor the ammonia in the chicken farm with self-power, it will save a lot of costs and reduce harm to the environment. In 2012, the invention of the friction nanogenerator (TENG) provided a low-cost and efficient environmental mechanical energy capture technology. In particular, the development of the rotating freestanding structure TENG provides a new method for efficiently capturing the breeze energy in the environment at low frequency, which is expected to be applied to self-powered ammonia monitoring in chicken farms.
[0004] Therefore, there is a need for a system that is cost-saving and can monitor the ammonia concentration in a chicken farm in real time. Summary of the invention
[0005] The main purpose of the present invention is to provide a chicken farm environment monitoring system to solve the problem that the chicken farm real-time monitoring system in the prior art is high in cost and cannot monitor the ammonia concentration.
[0006] To achieve the above objectives, the present invention provides a chicken farm environment monitoring system, including: TENG, a sensor, a microcontroller unit MCU, a wireless transmission module and a mobile terminal. The TENG powers the sensor, the microcontroller unit MCU and the wireless transmission module. The sensor detects the ammonia concentration in the chicken farm environment and transmits the ammonia concentration data to a data acquisition module of the microcontroller unit MCU. The microcontroller unit MCU uploads the ammonia concentration data to the mobile terminal through the wireless transmission module and displays the ammonia concentration data on the mobile terminal.
[0007] Furthermore, the sensor is Ga 2 O 3 / Mo 2 Ti 2 AlC 3 sensor.
[0008] Further, the preparation of Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The sensor method specifically comprises the following steps:
[0009] S1, first 0.2 mol Ga(NO 3 ) 3 xH2O was dissolved in 640 ml of distilled water, and then the solution was stirred evenly using a magnetic stirrer. 4 OH was added to the solution and the pH was adjusted to 9.
[0010] S2, adding the solution obtained in step S1 to a high-pressure reactor and heating it in a muffle furnace at 100° C. for 5 hours. After the reactor is naturally cooled to room temperature, the obtained white precipitate is washed twice with distilled water and ethanol in succession. The washed precipitate is then dispersed in 5 ml of distilled water and dried in a hot air oven at 75° C. for 8 hours to obtain GaOOH powder.
[0011] S3, placing the pure GaOOH powder sample obtained in step S2 in a tube furnace and calcining it at 1000°C for 5h to obtain white Ga 2 O 3 powder.
[0012] S4, 250 mesh molybdenum powder Mo, 325 mesh titanium powder Ti, 325 mesh aluminum powder Al and 300 mesh graphite powder C were mixed with zirconium oxide grinding balls in a molar ratio of 1.5:1.5:1.1:2 and stirred for 18 hours; additional aluminum powder Al was added to compensate for the evaporation of aluminum Al or oxidation to aluminum oxide Al 2 O 3 Part of Al.
[0013] Further, the preparation of Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The sensor method further comprises the steps of:
[0014] S5, take 1g of the mixed powder obtained in step S4 and 3g of Ga obtained in step S3. 2 O 3 The powder is placed in a covered Al 2 O 3The crucible was placed in a tube furnace and heated to 1600°C at a rate of 5°C / min and kept at this temperature for 4 h under flowing argon. After cooling in the furnace, the micro-sintered porous compact was ground into a fine powder using a tin-coated milling drill.
[0015] S6, slowly add 2 g of the powder obtained in step S5 into 40 mL of hydrofluoric acid HF solution, the concentration of the hydrofluoric acid solution is ≥49 wt%, the whole process is carried out in a 100 ml Teflon beaker, magnetic stirring at 50°C for 48 h, and centrifugal washing with deionized water until pH≈6.
[0016] S7, collect the precipitate, and dry it in vacuum at 50 °C for 12 h to obtain Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The composite powder was added to ethanol and dispersed, the dispersion was sonicated for 1 h, centrifuged at 10000 rpm for 10 min, and the obtained precipitate was sonicated with deionized water for 20 min.
[0017] S8, 1 ml of the supernatant was filtered with a polyvinylidene fluoride (PVDF) membrane and vacuum dried in a vacuum oven at 80°C for 8 h to obtain the composite Ga 2 O 3 / Mo 2 Ti 2 AlC 3 .
[0018] S9, Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The solution was dropped onto a polyaluminium silicate substrate to form a sensing film, which was then dried at 60 °C in vacuum for 4 h to obtain the Ga 2 O 3 / Mo 2 Ti 2 AlC 3 sensor.
[0019] Furthermore, TENG includes: a rotor and a stator located below the rotor, the rotor and the stator are circular, the rotor is a fan blade structure, and the fan blade structure is covered with a copper electrode; the stator includes: an acrylic substrate surface layer, a copper electrode layer and a Capton film, the copper electrode layer includes: a plurality of first electrode layers and a plurality of second electrode layers, the plurality of first electrode layers and the plurality of second electrode layers are cross-arranged and cross-covered in a grid shape on the surface of the acrylic substrate, the first electrode layers are all conductive, the second electrode layers are all conductive, there is a gap between the first electrode layer and the second electrode layer that is not conductive, and the copper electrode layer is covered with a Capton film as a triboelectric layer.
[0020] Furthermore, in the initial state, the copper electrode of the top rotor is aligned with the copper electrode layer of the left semicircle of the bottom stator, and electrons are transferred from the copper electrode surface of the top rotor to the surface of the Capton membrane, generating equal amounts of positive and negative charges on the copper electrode of the top rotor and the surface of the Capton membrane, respectively. At this time, the TENG is in an electrostatic equilibrium state, and no free electrons flow through the external circuit; as the rotor rotates, the overlapping area between the copper electrode of the top rotor and the copper electrode layer of the left semicircle decreases, and the potential difference drives the current to flow from the right semicircle copper electrode layer of the stator to the left semicircle copper electrode layer, thereby reaching a new electrostatic equilibrium; as the rotation continues, the charge transfer process continues until the copper electrode of the top rotor is completely aligned with the right semicircle copper electrode layer of the stator, at which time the current passing through the external circuit is 0; when the rotor continues to rotate, the overlapping area between the copper electrode of the top rotor and the left semicircle copper electrode layer of the stator gradually increases, generating a reverse current; the charge continues to be transferred until the copper electrode of the top rotor is completely aligned with the left semicircle copper electrode layer of the stator, and this reciprocating process generates alternating current in the external circuit.
[0021] Furthermore, the diameters of the rotor and stator of TENG are 10 cm.
[0022] Furthermore, the fan blade structure has 8 blades, and the stator has 16 copper electrode layers, namely 8 first electrode layers and 8 second electrode layers.
[0023] The present invention has the following beneficial effects:
[0024] The present invention is based on Ga 2 O 3 / Mo 2 Ti 2 AlC 3 Binary nanocomposites for the preparation of high-performance interdigitated electrodes for NH 3 Sensors and use them for self-powered chicken farms NH 3 Real-time monitoring of concentration. 2 O 3 and Ga 2 O 3 / Mo 2 Ti 2 AlC 3 Performance of ammonia gas sensors developed from two materials, Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The sensor showed better response. 2 O 3 / Mo 2 Ti 2 AlC3 The sensor also has excellent selectivity and repeatability. The simulation results based on DFT show that Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The charge transfer ratio in the material is Ga 2 O 3 The charge transfer in the material is stronger, and Ga 2 O 3 / Mo 2 Ti 2 AlC 3 Materials for NH 3 The adsorption of Mo is also better than that of the other two materials. 2 Ti 2 AlC 3 The nano-layered structure has the advantage of a large specific surface area, which can increase its affinity with Ga 2 O 3 The contact site is NH 3 Provide a large number of adsorption sites, effectively improving the composite material's NH 3 At the same time, the present invention also developed a self-starting chicken farm ammonia monitoring system powered by a stand-alone mode friction nanogenerator (TENG), which can collect wind energy in the environment and wirelessly transmit the ammonia concentration to a mobile terminal every period of time (30s to 60s) in a self-powered manner. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the specific implementation of the present invention or the technical solutions in the prior art, the following will briefly introduce the drawings required for the specific implementation or the prior art description. Obviously, the drawings described below are some implementations of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the drawings:
[0026] Figure 1 The preparation of Ga 2 O 3 / Mo 2 Ti 2 AlC 3 Flowchart of the sensor.
[0027] Figure 2 Shows Mo 2 Ti 2 AlC 3 SEM image of the material at a resolution of 2 μm.
[0028] Figure 3 Shows Mo 2Ti 2 AlC 3 SEM image of the material at a resolution of 5 μm.
[0029] Figure 4 It shows that Ga 2 O 3 SEM image of the material at a resolution of 10 μm.
[0030] Figure 5 It shows that Ga 2 O 3 / Mo 2 Ti 2 AlC 3 SEM image of the material at a resolution of 10 μm.
[0031] Figure 6 It shows that Ga 2 O 3 Material,Mo 2 Ti 2 AlC 3 Materials and Ga 2 O 3 / Mo 2 Ti 2 AlC 3 XRD spectrum of the material.
[0032] Figure 7 It shows that Ga 2 O 3 Material, Mo 2 Ti 2 AlC 3 Materials and Ga 2 O 3 / Mo 2 Ti 2 AlC 3 Raman spectra of materials.
[0033] Figure 8 It shows that Ga 2 O 3 Material, Mo 2 Ti 2 AlC 3 Materials and Ga 2 O 3 / Mo 2 Ti 2 AlC 3 FTIR spectra of the materials.
[0034] Fig. 9 It shows that Ga 2 O 3 / Mo 2 Ti 2AlC 3 Sensors in different NH 3 Resistance curves under concentration.
[0035] Fig.10 It shows that Ga 2 O 3 / Mo 2 Ti 2 AlC 3 Sensors in different NH 3 Concentration response curve.
[0036] Fig.11 Ga 2 O 3 and Ga 2 O 3 / Mo 2 Ti 2 AlC 3 Sensors in different NH 3 Fitting curve of the response under concentration.
[0037] Fig.12 It shows that Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The response or recovery time curve of the sensor.
[0038] Fig.13 Ga 2 O 3 / Mo 2 Ti 2 AlC 3 Resistance curve of the sensor at different temperatures.
[0039] Fig.14 It shows that Ga 2 O 3 / Mo 2 Ti 2 AlC 3 Response curves of the sensor at different humidity levels.
[0040] Fig.15 Ga 2 O 3 / Mo 2 Ti 2 AlC 3 Plot of sensor response to different gases.
[0041] Fig.16 It shows that Ga 2 O 3 / Mo 2 Ti2 AlC 3 Repeatability test curve of the sensor at 1ppm.
[0042] Fig.17 It shows that Ga 2 O 3 / Mo 2 Ti 2 AlC 3 Sensors in different NH 3 Stability curves at different concentrations.
[0043] Fig.18 Shows Mo 2 Ti 2 AlC 3 The sensor absorbs NH 3 The charge density diagram of .
[0044] Fig.19 It shows that Ga 2 O 3 The sensor absorbs NH 3 The charge density diagram of .
[0045] Fig. 20 It shows that Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The sensor absorbs NH 3 The charge density diagram of .
[0046] Fig.21 Shows Mo 2 Ti 2 AlC 3 , Ga 2 O 3 and Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The sensor adsorbs NH 3 The total density of states (TDOS) before.
[0047] Fig. 22 It shows that Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The sensor adsorbs NH 3 Comparison chart of TDOS before and after.
[0048] Fig.23 It shows that Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The sensor adsorbs NH 3 The projected density of states (PDOS) of a molecule.
[0049] Fig.24 The rotor structure diagram of TENG is shown.
[0050] Fig.25 shows the stator structure diagram of TENG.
[0051] Fig.26 The voltage curves of TENG at different rotation speeds are shown.
[0052] Fig. 27 The curve of the peak voltage of TENG changing with the rotation speed is shown.
[0053] Fig.28 The current curves of TENG at different rotation speeds are shown.
[0054] Fig.29 The curve of the peak current of TENG changing with the rotation speed is shown.
[0055] Fig.30 The voltage curve of TENG at a rotation speed of 105 pm is shown.
[0056] Fig.31 The curves showing the peak voltage and current of the external resistor as a function of the resistance value are shown.
[0057] Fig.32 The curve showing the change of the peak power of TENG with the resistance value of the external load is shown.
[0058] Fig.33 The voltage curves of TENG charging 220μF, 330μF and 470μF capacitors are shown.
[0059] Fig.34 A graph showing the voltage durability of the TENG.
[0060] Fig.35 The Ga powered by TENG is shown 2 O 3 / Mo 2 Ti 2 AlC 3 The voltage of the sensor is different in NH 3 The concentration change curve.
[0061] The reference numerals in the above drawings are:
[0062] 10. rotor; 20. stator; 21. first electrode layer; 22. second electrode layer. DETAILED DESCRIPTION
[0063] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0064] A chicken farm environment monitoring system comprises: a TENG, a sensor, a microcontroller unit MCU, a wireless transmission module and a mobile terminal. The TENG supplies power to the sensor, the microcontroller unit MCU and the wireless transmission module. The sensor detects the ammonia concentration in the chicken farm environment and transmits the ammonia concentration data to a data acquisition module of the microcontroller unit MCU. The microcontroller unit MCU uploads the ammonia concentration data to the mobile terminal through the wireless transmission module and displays the ammonia concentration data on the mobile terminal.
[0065] Specifically, the sensor is Ga 2 O 3 / Mo 2 Ti 2 AlC 3 sensor.
[0066] Specifically, Figure 1 As shown, the preparation of Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The sensor method specifically comprises the following steps:
[0067] S1, first 0.2 mol Ga(NO 3 ) 3 xH2O was dissolved in 640 ml of distilled water, and then the solution was stirred evenly using a magnetic stirrer. 4 OH was added to the solution and the pH was adjusted to 9.
[0068] S2, adding the solution obtained in step S1 to a high-pressure reactor and heating it in a muffle furnace at 100° C. for 5 hours. After the reactor is naturally cooled to room temperature, the obtained white precipitate is washed twice with distilled water and ethanol in succession. The washed precipitate is then dispersed in 5 ml of distilled water and dried in a hot air oven at 75° C. for 8 hours to obtain GaOOH powder.
[0069] S3, placing the pure GaOOH powder sample obtained in step S2 in a tube furnace and calcining it at 1000°C for 5h to obtain a white Ga 2 O 3 powder.
[0070] S4, 250 mesh molybdenum powder Mo, 325 mesh titanium powder Ti, 325 mesh aluminum powder Al and 300 mesh graphite powder C were mixed with zirconium oxide grinding balls in a molar ratio of 1.5:1.5:1.1:2 and stirred for 18 hours; additional aluminum powder Al was added to compensate for the evaporation of aluminum Al or oxidation to aluminum oxide Al 2 O 3 Part of Al.
[0071] Specifically, the preparation of Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The sensor method further comprises the steps of:
[0072] S5, take 1g of the mixed powder obtained in step S4 and 3g of Ga obtained in step S3. 2 O 3 The powder is placed in a covered Al 2 O 3 The crucible was placed in a tube furnace and heated to 1600°C at a rate of 5°C / min and kept at this temperature for 4 h under flowing argon. After cooling in the furnace, the micro-sintered porous compact was ground into a fine powder using a tin-coated milling drill.
[0073] S6, slowly add 2 g of the powder obtained in step S5 into 40 mL of hydrofluoric acid HF solution, the concentration of the hydrofluoric acid solution is ≥49 wt%, the whole process is carried out in a 100 ml Teflon beaker, magnetic stirring at 50°C for 48 h, and centrifugal washing with deionized water until pH≈6.
[0074] S7, collect the precipitate, and dry it in vacuum at 50 °C for 12 h to obtain Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The composite powder was added to ethanol and dispersed, the dispersion was sonicated for 1 h, centrifuged at 10000 rpm for 10 min, and the obtained precipitate was sonicated with deionized water for 20 min.
[0075] S8, 1 ml of the supernatant was filtered with a polyvinylidene fluoride (PVDF) membrane and vacuum dried in a vacuum oven at 80°C for 8 h to obtain the composite Ga 2 O 3 / Mo 2 Ti 2 AlC 3 .
[0076] S9, Ga2 O 3 / Mo 2 Ti 2 AlC 3 The solution was dropped onto a polyaluminium silicate substrate to form a sensing film, which was then dried at 60 °C in vacuum for 4 h to obtain the Ga 2 O 3 / Mo 2 Ti 2 AlC 3 Sensor. The interdigitated electrodes are printed on a flexible polyimide substrate using planar rigid printed circuit board technology.
[0077] In order to verify the Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The ability of the sensor to monitor ammonia was characterized by scanning electron microscopy (SEM). 2 Ti 2 AlC 3 , Ga 2 O 3 and Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The surface morphology of the composite material. Figure 2 and Figure 3 As shown, Mo 2 Ti 2 AlC 3 The layered structure of the nanosheets has a large lateral size and specific surface area, which can provide numerous adsorption sites for the adsorption of ammonia. 2 O 3 It is a rod-shaped powder with a diameter of about 1-2 μm, such as Figure 4 As shown. Figure 5 As shown in Ga 2 O 3 / Mo 2 Ti 2 AlC 3 In the SEM image of the composite material, Ga 2 O 3 Nanorods and Mo 2 Ti 2 AlC 3 The nanosheets are intertwined, which characterizes the Ga 2 O 3 / Mo 2 Ti 2 AlC 3 Successful preparation of composite materials.
[0078] From Ga 2 O 3 and Mo 2 Ti 2 AlC 3 Many diffraction peaks can be seen in the X-ray diffraction (XRD) pattern of the material within the scanning range of 10° to 80°, which matches the standard pattern (JCPDS #00-041-1103). Figure 6 As shown, Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The XRD spectrum contains Ga 2 O 3 and Mo 2 Ti 2 AlC 3 All the diffraction peaks of the material prove that Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The composite material was successfully synthesized. 2 O 3 The β phase is formed with lattice parameters of a = 12.24 Å, b = 3.02 Å, and c = 5.79 Å. Ga 2 O 3 There are three groups of optical phonon vibration modes, namely the stretching and bending modes of tetrahedral related phonons (600 ~ 800 cm 2 ), the in-plane deformation of the octahedral related phonons (300 ~ 500 cm 2 ) and the liberation and translational phonon vibration modes of tetrahedral-octahedral chains (100 ~ 300 cm 2 ). 2 Ti 2 AlC 3 The Raman spectra at 232 and 312 cm -1 The characteristic peaks appearing at Fan also appear in Ga 2 O 3 / Mo 2 Ti 2 AlC 3 In composite materials, such as Figure 7 shown. Ga 2 O 3 The Fourier transform infrared (FTIR) spectrum of the sample showed that the adsorbed water molecules (deformation vibration peak at 1630 cm -1 ), and OH groups (Ga-OH bending vibration peak at 1350 cm -1 ) exists.2 O 3 450 cm of the sample -1 and 692 cm -1 The two complex peaks are Ga 2 O 3 Typical features of the lattice structure. Mo 2 Ti 2 AlC 3 The sample was at 3700 cm -1 The absorption peak is Mo 2 Ti 2 AlC 3 Typical features of the lattice structure. 2 O 3 / Mo 2 Ti 2 AlC 3 The FTIR absorption peak of the composite material includes Ga 2 O 3 and Mo 2 Ti 2 AlC 3 The characteristic peaks of the sample, such as Figure 8 shown.
[0079] In order to characterize the performance of the sensor, the Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The sensors were placed in six different NH 3 The sensor resistance is tested in each NH 3 After the resistance is restored to the initial value, put it into the next concentration of NH 3 Test in.
[0080] Based on Ga 2 O 3 / Mo 2 Ti 2 AlC 3 Composite materials and pure Ga-based 2 O 3 The resistance of the sensor material increases with the NH 3 The concentration of Ga increases. 2 O 3 and Ga 2 O 3 / Mo 2 Ti 2 AlC 3The resistance of the sensor at 0ppm is about 5GΩ and 40MΩ, respectively, which indicates that Mo 2 Ti 2 AlC 3 The resistance of the sensor after doping is lower. The sensor with reduced resistance is more conducive to adapting to the circuit for monitoring, such as Fig. 9 In order to better quantify and compare the performance of the sensor, the sensor was placed in different NH 3 The resistance change under the concentration is converted into a response. The response of both sensors gradually increases with the increase of ammonia concentration. 2 O 3 / Mo 2 Ti 2 AlC 3 The sensor response is higher than Ga 2 O 3 sensor, which indicates that the composite material has a better ammonia sensing effect, e.g. Fig.10 Response The calculation method is as follows:
[0081] (1);
[0082] in, The sensor is in a certain NH 3 Resistance at concentration. Ga is the resistance of the sensor in 0ppm ammonia. 2 O 3 and Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The fitting formulas of the sensors are Y=136.9-111.7*0.77 X and Y=97.5-109.9*0.73 X , which is NH 3 At the same time, their fitting coefficients (R2) all reached above 0.99, indicating that the fitting formula is very accurate. Fig.11 shown.
[0083] In order to characterize the response speed of the sensor, the Ga 2 O 3 / Mo 2 Ti 2 AlC 3 Sensors in NH 3 Response / recovery curve at 1.5 ppm concentration. The response / recovery time refers to the time taken for the response value to rise from the stable response value to 90%, and the time taken for the stable response value to fall to 10%.2 O 3 / Mo 2 Ti 2 AlC 3 The response and recovery times of the sensor are 17s and 43s respectively. Fig.12 As shown. By the previous NH 3 Sensor comparison, Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The sensor has certain advantages in response and response / recovery time. As the temperature gradually increases from 15°C to 29°C, the resistance value of the sensor increases linearly. However, the effect of temperature on the resistance value is not significant, which indicates that temperature fluctuations under room temperature have little effect on sensing. Temperature correction can be used to improve Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The accuracy of the sensor, such as Fig.13 As shown in the figure, humidity changes in the environment will also interfere with the accurate detection of the sensor, so we tested the response of the sensor in the range of 0% relative humidity (RH) to 97% RH. 2 O 3 / Mo 2 Ti 2 AlC 3 The response of the sensor is linear with the increase of humidity, and the fitting curve is Y=0.1826+0.0709X, as shown in Fig.14 Similarly, in the actual ammonia monitoring scenario, based on the humidity fitting curve, the accuracy of ammonia sensing can be further improved by calibrating the humidity sensor. 2 O 3 / Mo 2 Ti 2 AlC 3 The sensor is sensitive to 1 ppm NH 3 The response of the gas is much higher than that of acetone, nitrogen dioxide, hydrogen sulfide, sulfur dioxide, carbon monoxide and other gases, such as Fig.15 In the repeatability test experiment, Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The sensor response value does not change much, indicating that the sensor has good repeatability, such as Fig.16 As shown. In NH 3The sensor response was measured every 10 days for 60 days at concentrations of 0.5 ppm, 1.5 ppm, and 3 ppm. 2 O 3 / Mo 2 Ti 2 AlC 3 Sensors in different NH 3 The response deviation at different concentrations was less than 5%, which indicates excellent long-term stability. Fig.17 shown.
[0084] Based on the density functional theory (DFT) 2 O 3 、Mo 2 Ti 2 AlC 3 and Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The ammonia-sensitive properties of the composites were calculated and analyzed. 3 The absorption on the three materials was compared. These calculations were performed using the DMol3 code included in the Materials Studio 8.0 software package. The NH 3 In Ga 2 O 3 、Mo 2 Ti 2 AlC 3 and Ga 2 O 3 / Mo 2 Ti 2 AlC 3 Molecular models and charge density diagrams of surface adsorption, such as Fig.18 , Fig.19 , Fig. 20 In contrast, Mo 2 Ti 2 AlC 3 Materials for NH 3 The affinity of Ga 2 O 3 and Ga 2 O 3 / Mo 2 Ti 2 AlC 3 With NH 3 The chemical bond of Ga 2 O 3 / Mo 2 Ti2 AlC 3 The charge transfer ratio in the system is Ga 2 O 3 The charge transfer in the system is stronger. The adsorption energy of the material is calculated using the following formula:
[0085] (2);
[0086] in, is the energy of the entire system, It's Ga 2 O 3 、Mo 2 Ti 2 AlC 3 and or Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The energy Yes NH 3 Energy of the molecule. As shown in Table 1, Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The adsorption energy (E ad ) is -1.614 eV, exceeding Mo 2 Ti 2 AlC 3 and Ga 2 O 3 Therefore, with Mo 2 Ti 2 AlC 3 and Ga 2 O 3 In comparison, Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The nanocomposites showed better NH 3 Adsorption capacity.
[0087] Table 1 Ga 2 O 3 、Mo 2 Ti 2 AlC 3 and Ga 2 O 3 / Mo 2 Ti 2 AlC 3 Parameters involved in the comparison system of materials before and after ammonia adsorption
[0088] .
[0089] In addition, from the total density of states of the three materials, such as Fig.21 It can be seen that Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The electron density curve of Ga 2 O 3 Compared to moving to the left, this is due to Mo 2 Ti 2 AlC 3 Effect of doping. NH 3 After adsorption, Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The electron density peaks in the TDOS diagram of are slightly weakened in many places, such as Fig. 22 shown. Ga 2 O 3 / Mo 2 Ti 2 AlC 3 The change in the projected density of states (PDOS) of the material is mainly attributed to the interaction between the Ti 3d orbital, Ga 3d, C 2p orbital, and O 2p orbital. These orbitals have obvious overlapping peaks at -15.7 eV, -4.0 eV, and -0.6 eV, which indicates that NH 3 Molecules and Ga 2 O 3 / Mo 2 Ti 2 AlC 3 There is strong hybridization between nanocomposites, e.g. Fig.23 shown.
[0090] At room temperature, Ga 2 O 3 About NH 3 The sensing mechanism is attributed to the dissociative sensing mechanism of water vapor and the role of surface adsorbed oxygen. On the one hand, according to the thermodynamic equilibrium conditions, water molecules are dissociated and adsorbed on the metal oxide surface in the form of H+ and OH- on its affinity sites. 2 O in Ga 2 O 3 The dissociative adsorption on Ga is believed to promote the formation of a Ga-OH dipole, leaving a lattice oxygen vacancy and donating a pair of free electrons.
[0091] As the system further interacts with water, Ga2 O 3 A water layer forms on top of the sensing material, which is in the NH 3 When the molecules are present, they act as liquid electrolytes. In the presence of H+ and OH- ions, NH 3 Dissociate into and OH-, and changes the pH value of the surface electrolyte layer, which leads to changes in the electronic and ionic conduction of the active material surface. 3 After the molecules are adsorbed, they will be Ga 2 O 3 The lattice donates an electron, which causes the resistance of the sensor film to decrease.
[0092] On the other hand, O in the air 2 Due to its relatively high electron affinity, it can be obtained from Ga 2 O 3 The surface captures electrons, thus increasing the depletion layer thickness and causing an increase in resistance. 3 When adsorbed on these oxygen adsorption sites, NH 3 Donating electrons to Ga 2 O 3 lattice, thereby reducing the resistance of the sensing film.
[0093] It can be concluded that the more adsorption active sites there are, the greater the sensing response. Therefore, materials with relatively large size and large surface-to-volume ratio can show better sensing response. Therefore, the two-dimensional material Mo with high specific surface area 2 Ti 2 AlC 3 The doping of Mo can significantly improve the ammonia sensitivity of the composite sensor. 2 Ti 2 AlC 3 The multilayered nanostructure has the advantage of large specific surface area, which can increase its affinity with Ga 2 O 3 The contact site is NH 3 Provide a large number of adsorption sites, effectively improving the composite material's NH 3 Response.
[0094] Specifically, Fig.24 and Fig.25As shown, TENG includes: a rotor 10 and a stator 20 located below the rotor, the rotor and the stator are circular, the rotor is a fan blade structure, and the fan blade structure is covered with copper electrodes; the stator includes: an acrylic substrate surface layer, a copper electrode layer and a Capton film, the copper electrode layer includes: a plurality of first electrode layers 21 and a plurality of second electrode layers 22, the plurality of first electrode layers and the plurality of second electrode layers are cross-arranged and cross-covered on the surface of the acrylic substrate in a grid shape, the first electrode layers are all conductive, the second electrode layers are all conductive, there is a gap between the first electrode layer and the second electrode layer that is not conductive, and the copper electrode layer is covered with a Capton film as a triboelectric layer.
[0095] Specifically, in order to capture the breeze energy in the environment, the present invention manufactures a rotating TENG with an independent structure. The working principle of TENG is based on the coupling of contact electrification and electrostatic induction. In the initial state, the copper electrode of the top rotor is aligned with the copper electrode layer of the left semicircle of the bottom stator, and electrons are transferred from the copper electrode surface of the top rotor to the surface of the Capton membrane, generating equal amounts of positive and negative charges on the top copper electrode and the surface of the Capton membrane, respectively. At this time, the TENG is in an electrostatic equilibrium state, and no free electrons flow through the external circuit. As the rotor rotates, the overlapping area between the copper electrode of the top rotor and the copper electrode layer of the left semicircle decreases, and the potential difference drives the current to flow from the copper electrode layer of the right semicircle of the stator to the copper electrode layer of the left semicircle, thereby achieving a new electrostatic equilibrium. As the rotation continues, the charge transfer process continues until the copper electrode of the top rotor is completely aligned with the copper electrode layer of the right semicircle of the stator, at which time the current passing through the external circuit is 0. As the rotor continues to rotate, the overlapping area between the top copper electrode and the copper electrode layer of the left semicircle of the stator gradually increases, generating a reverse current. Charge continues to be transferred until the top copper electrode is completely aligned with the copper electrode layer of the left semicircle of the stator, thereby generating alternating current in the external circuit.
[0096] Specifically, the diameters of the rotor and stator of TENG are 10 cm.
[0097] Specifically, the fan blade structure has 8 blades, and the stator has 16 copper electrode layers, namely 8 first electrode layers and 8 second electrode layers.
[0098] As the rotation speed of TENG gradually increases from 5 rpm to 115 rpm, the peak-to-peak value of the open circuit voltage (Voc) gradually increases from 851 V to 1337 V. Fig.26 The voltage Voc of TENG reaches saturation in the speed range of 85-115 rpm, which is attributed to the rapid induction and dissipation of charge under high-frequency contact, as shown in Fig. 27 The difference is that as the speed gradually increases from 5rpm to 115rpm, the peak value of the short-circuit current (Isc) of TENG increases almost linearly from 0.69μA to 6.84μA, as shown in Figure 2. Fig.28 Shown and Fig.29 As shown in Figure 2, the Voc of TENG shows a very regular periodic alternating current, such as Fig.30 As shown in Figure 2, the TENG is used to power a resistor and measure the voltage on the resistor and the current in the circuit. As the resistance increases, the voltage and current increase and decrease, respectively, as shown in Figure 2. Fig.31 As shown in Figure 2, the output power of TENG calculated based on voltage and current first increases and then decreases with the increase of load resistance. When the load resistance is 20 MΩ, the output power of TENG reaches a maximum value of 1.68 mW, as shown in Figure 2. Fig.32 As shown in Figure 2. At a speed of 105 rpm, after the TENG is rectified and stepped down, it charges the 220, 330, and 470 μF capacitors for 60 seconds, and their voltages reach 3.1, 3.3, and 5.9 V, respectively. Fig.33 At a rotation speed of 65 rpm, even after 2 hours of testing, the Voc of TENG has almost no change, as shown in Figure 2. Fig.34 shown.
[0099] The Ga provided by the present invention 2 O 3 / Mo 2 Ti 2 AlC 3 The sensor is flexible and can be attached to any place with different bending degrees. 2 O 3 / Mo 2 Ti 2 AlC 3 The sensor is mounted on the PCB, and the voltage change of the sensor is tested at 0ppm and 3ppm ammonia concentration. It can be seen that the voltage change of the sensor can directly represent the change of ammonia concentration in the environment, thereby realizing self-powered ammonia sensing. Fig.35 As shown. In order to achieve fully self-driven ammonia concentration monitoring and wireless transmission, the present invention proposes a power management strategy for the developed TENG. It includes a rectifier and step-down module, an energy storage capacitor, a voltage management module, a data acquisition module and a wireless transmission module. In view of the characteristics of TENG alternating current and high voltage, the electric energy is stored in the capacitor after rectification and step-down. When the voltage in the capacitor reaches 4V, the voltage management module will be turned on to supply electric energy to the microcontroller unit (MCU) and the wireless transmission module. The ammonia sensor data is finally displayed on the terminal. After the voltage on the energy storage capacitor reaches 4V, the MCU and the wireless transmission module will obtain a stable voltage of 2.5V for 0.18s, which is sufficient for them to complete the collection and wireless transmission of ammonia sensor data. A fan is used to simulate environmental wind energy to drive TENG to power the system, and the data of the sensor in the air bottle and the ammonia bottle are tested. The system transmits ammonia sensor data to the terminal approximately every 35s.
[0100] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.
Claims
1. A chicken farm environment monitoring system, characterized in that: include: TENG, sensor, microcontroller unit MCU, wireless transmission module and mobile terminal, wherein the TENG is used to power the sensor, microcontroller unit MCU and wireless transmission module, the sensor detects the ammonia concentration in the chicken farm environment, and transmits the ammonia concentration data to the data acquisition module of the microcontroller unit MCU, the microcontroller unit MCU uploads the ammonia concentration data to the mobile terminal through the wireless transmission module, and displays the ammonia concentration data on the mobile terminal; The sensor is a Ga2O3 / Mo2Ti2AlC3 sensor; The method for preparing the Ga2O3 / Mo2Ti2AlC3 sensor specifically comprises the following steps: S1, first dissolve 0.2 mol Ga(NO3)3·xH2O in 640 ml distilled water, then stir the solution evenly using a magnetic stirrer, add NH4OH to the solution, and adjust the pH value to 9; S2, adding the solution obtained in step S1 to a high-pressure reactor and heating it in a muffle furnace at a temperature of 100° C. for 5 hours. After the reactor is naturally cooled to room temperature, the obtained white precipitate is washed twice with distilled water and ethanol in succession, and then the washed precipitate is dispersed in 5 ml of distilled water, and dried in a hot air oven at 75° C. for 8 hours to obtain GaOOH powder; S3, placing the pure GaOOH powder sample obtained in step S2 in a tube furnace and calcining at 1000° C. for 5 h to obtain white Ga2O3 powder; S4, 250 mesh molybdenum powder Mo, 325 mesh titanium powder Ti, 325 mesh aluminum powder Al and 300 mesh graphite powder C were mixed with zirconium oxide grinding balls in a molar ratio of 1.5:1.5:1.1:2 and stirred for 18 hours; additional aluminum powder Al was added to compensate for the evaporation of aluminum Al or part of Al oxidized to aluminum oxide Al2O3; The method for preparing the Ga2O3 / Mo2Ti2AlC3 sensor also includes the following steps: S5, taking 1 g of the screened mixture powder obtained in step S4 and 3 g of the Ga2O3 powder obtained in step S3, placing them in a covered Al2O3 crucible, placing the crucible in a tube furnace, heating to 1600°C at a rate of 5°C / min, and keeping the temperature under flowing argon for 4 hours, and after cooling in the furnace, grinding the micro-sintered porous compact into fine powder using a tin-plated milling drill bit; S6, slowly add 2 g of the powder obtained in step S5 into 40 mL of hydrofluoric acid HF solution, the concentration of the hydrofluoric acid solution is ≥49 wt %, the whole process is carried out in a 100 ml Teflon beaker, magnetically stirred at 50 ° C for 48 h, and washed by centrifugation with deionized water until the pH is ≈ 6; S7, collect the precipitate, vacuum dry it at 50 °C for 12 h to obtain Ga2O3 / Mo2Ti2AlC3 powder, add the composite powder to ethanol and disperse it, ultrasonically treat the dispersion for 1 h, centrifuge it at 10000 rpm for 10 min, and ultrasonically treat the precipitate with deionized water for 20 min; S8, 1 ml of the supernatant was filtered with a polyvinylidene fluoride (PVDF) membrane and vacuum dried in a vacuum oven at 80°C for 8 h to obtain the composite Ga2O3 / Mo2Ti2AlC3; S9, the Ga2O3 / Mo2Ti2AlC3 solution was dropped onto the polyaluminum silicate substrate through an interdigitated electrode to form a sensing film, and then the Ga2O3 / Mo2Ti2AlC3 sensor was obtained after vacuum drying at 60 °C for 4 h.
2. A chicken farm environment monitoring system according to claim 1, characterized in that: TENG includes: a rotor and a stator located below the rotor, the rotor and the stator are circular, the rotor is a fan blade structure, and the fan blade structure is covered with copper electrodes; the stator includes: an acrylic substrate surface layer, a copper electrode layer and a Capton film, the copper electrode layer includes: multiple first electrode layers and multiple second electrode layers, the multiple first electrode layers and the multiple second electrode layers are cross-arranged and cross-covered on the surface of the acrylic substrate in a grid shape, the first electrode layers are all conductive, the second electrode layers are all conductive, there is a gap between the first electrode layer and the second electrode layer that is not conductive, and the copper electrode layer is covered with a Capton film as a triboelectric layer.
3. A chicken farm environment monitoring system according to claim 2, characterized in that: In the initial state, the copper electrode of the top rotor is aligned with the copper electrode layer of the left semicircle of the bottom stator, and electrons are transferred from the copper electrode surface of the top rotor to the surface of the Capton membrane, generating equal amounts of positive and negative charges on the copper electrode of the top rotor and the surface of the Capton membrane, respectively. At this time, the TENG is in an electrostatic equilibrium state, and no free electrons flow through the external circuit. As the rotor rotates, the overlapping area between the copper electrode of the top rotor and the copper electrode layer of the left semicircle decreases, and the potential difference drives the current to flow from the copper electrode layer of the right semicircle of the stator to the copper electrode layer of the left semicircle, thereby reaching a new electrostatic equilibrium. As the rotation continues, the charge transfer process continues until the copper electrode of the top rotor is completely aligned with the copper electrode layer of the right semicircle of the stator, at which time the current passing through the external circuit is 0. As the rotor continues to rotate, the overlapping area between the copper electrode of the top rotor and the copper electrode layer of the left semicircle of the stator gradually increases, generating a reverse current. Charge continues to be transferred until the copper electrode of the top rotor is completely aligned with the copper electrode layer of the left semicircle of the stator, and this reciprocating process generates alternating current in the external circuit.
4. A chicken farm environment monitoring system according to claim 3, characterized in that: The diameters of the rotor and stator of TENG are 10 cm.
5. A chicken farm environment monitoring system according to claim 4, characterized in that: The fan blade structure has 8 blades and the stator has 16 copper electrode layers, namely 8 first electrode layers and 8 second electrode layers.
Citation Information
Patent Citations
In-situ self-powered ammonia gas monitoring and alarming system
CN118130567A
Ammonia detection system for chicken farm
CN213364642U